Emotional problems across development: examining measurement invariance across childhood, adolescence and early adulthood. - Riglin, Lucy; Dennison, Charlotte; Martin, Joanna; Tseliou, Foteini; Armitage, Jessica M; Shakeshaft, Amy; Heron, Jon; Tilling, Kate; Thapar, Anita; Collishaw, Stephan (European Child & Adolescent Psychiatry, 2024)
Emotional problems (anxiety, depression) are prevalent in children, adolescents and young adults with varying ages at onset. Studying developmental changes in emotional problems requires repeated assessments using the same or equivalent measures. The parent-rated Strengths and Difficulties Questionnaire is commonly used to assess emotional problems in childhood and adolescence, but there is limited research about whether it captures a similar construct across these developmental periods. Our study addressed this by investigating measurement invariance in the scales' emotional problems subscale (SDQ-EP) across childhood, adolescence and early adulthood. Data from two UK population cohorts were utilised: the Millennium Cohort Study (ages 3–17 years) and the Avon Longitudinal Study of Parents and Children (4–25 years). In both samples we observed weak (metric) measurement invariance by age, suggesting that the parent-rated SDQ-EP items contribute to the underlying construct of emotional problems similarly across age. This supports the validity of using the subscale to rank participants on their levels of emotional problems in childhood, adolescence and early adulthood. However strong (scalar) measurement invariance was not observed, suggesting that the same score may correspond to different levels of emotional problems across developmental periods. Comparisons of mean parent-rated SDQ-EP scores across age may therefore not be valid.